2017
DOI: 10.1103/physrevc.96.014615
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic description of production cross sections including deexcitation effects

Abstract: Background: At the forefront of the nuclear science, production of new neutron-rich isotopes is continuously pursued at accelerator laboratories all over the world. To explore the currently-unknown territories in the nuclear chart far away from the stability, reliable theoretical predictions are inevitable.Purpose: To provide a reliable prediction of production cross sections taking into account secondary deexcitation processes, both particle evaporation and fission, a new method called TDHF+GEMINI is proposed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 105 publications
(165 reference statements)
3
91
0
Order By: Relevance
“…A number of theoretical approaches have been developed that describe the quasifission in terms of multi-nucleon transfer (MNT) processes [41,42,43,44,45,46,47]. Recently, time-dependent Hartree-Fock (TDHF) theory have proven to be an excellent tool for studying QF dynamics, and in particular mass-angle distributions and final fragment total kinetic energies (TKE) [48,31,37,49,32,50,51,52,34,53,45,54,55,56]. While the fragments produced in TDHF studies are the excited primary fragments [57] a number of extensions based on the use of Langevin dynamics have been successfully applied to de-excite these fragments [55,58,59,56,60] Theoretical studies of quasifission dynamics have taught us that dynamics themselves may be dominated by shell effects [61,47].…”
Section: Introductionmentioning
confidence: 99%
“…A number of theoretical approaches have been developed that describe the quasifission in terms of multi-nucleon transfer (MNT) processes [41,42,43,44,45,46,47]. Recently, time-dependent Hartree-Fock (TDHF) theory have proven to be an excellent tool for studying QF dynamics, and in particular mass-angle distributions and final fragment total kinetic energies (TKE) [48,31,37,49,32,50,51,52,34,53,45,54,55,56]. While the fragments produced in TDHF studies are the excited primary fragments [57] a number of extensions based on the use of Langevin dynamics have been successfully applied to de-excite these fragments [55,58,59,56,60] Theoretical studies of quasifission dynamics have taught us that dynamics themselves may be dominated by shell effects [61,47].…”
Section: Introductionmentioning
confidence: 99%
“…[42,43,51]. This force has been widely used in the fully three-dimensional TDHF calculations in heavy-ion collisions [34][35][36]42,43,[49][50][51]56,57,[59][60][61].…”
Section: Resultsmentioning
confidence: 99%
“…The cross sections for secondary products can be used for a direct comparison with the experimental measurement. In present calculation, we employ the default parameter setting in GEMINI++ code, as did in most calculations [60,61,63]. We have also tested the dependence of decay probability on the Monte-Carlo simulation times M event , and found that the decay probabilities are nearly identical for M event =1000 and 10000.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations